External Parasites of Dairy Cattle - Phillip E. Kaufman; Philip G. Koehler; Jerry F. Butler (EDIS)
This document is ENY-251 (IG050), one of a series of the Department of Entomology and Nematology, UF/IFAS Extension. Original publication date May 1999. Revised March 2006.